(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Purpose: To describe a case of spontaneous closure of a macular microhole induced by an acute posterior vitreous detachment (PVD). Methods: Retrospective case report and analysis of patient data. Case Report: We present a case of spontaneous closure of a posterior vitreous detachment (PVD) induced macular microhole. In our patient, macular microhole developed a few weeks after acute PVD. The development of macular hole secondarily to acute PVD is rare, and there are reports of spontaneous closure. Reporting this case is important to alert clinicians to the potential self-resolving nature of this pathology. Conclusion: Macular hole is a rare complication of acute PVD. Some cases resolve spontaneously without the need for surgical correction. A conservative approach may be an appropriate setting if no high-risk features are present.